Temperature and pressure changes of the "collision factor" in Schaaffs' molecular-kinetic theory of wave propagation in liquids - SOCZKIEWICZ, Eugeniusz (Archives of Acoustics, 1978)
Expressions have been derived which describe the pressure coefficient and temperature coefficient at constant pressure and volume of the "collision factor" s which determines, in Schaaffs' molecular-kinetic theory, the values of the velocity and attenuation coefficient of ultrasonic waves propagating in liquid. The values of the former coefficients have been determined for homologous series of saturated hydrocarbons, alkyl iodides, and benzene derivatives.